Analysis of the Optimal Number of Workforce Using the Theory of Constraints Approach in UKM Weeka Wedang Uwuh - Nurdin, Riani; Santoso, Prasidananto Nur; Gunawan, Gunawan; Mauidzoh, Uyuunul; Astuti, Marni; Kusumaningrum, Maria Deny (OPSI, 2024)
The increasing demand for wedang uwuh during the pandemic requires Weeka Wedang Uwuh as a producer to be quick and responsive in meeting demand. Competition for sales of wedang uwuh is currently quite tight because there are more and more wedang uwuh producers. One way to anticipate current business competition, especially in the herbal beverage industry, is to try to manage the resources owned by SMEs, including labor. The right number of workers will guarantee product availability and also provide minimum costs for labor costs. This research aims to provide suggestions for determining the optimal number of workers in order to minimize labor costs. ToC is a problem solving approach that focuses on eliminating constraints using available methodologies. Therefore, this approach is very suitable for eliminating obstacles at Weeka Wedang Uwuh in order to determine the optimal number of workers. To support the TOC approach, the Dynamic Program method will be applied to the obstacle removal step. The optimal number of workers in UKM Weeka Wedang Uwuh will be obtained by reducing 5 (five) workers in the Wedang Uwuh packing section. The savings that occurred during the research time period were Rp. 21,500,302.00 compared to expenses if it had the current number of workers.